The Effect of Service Quality on Muzakki Decision-Making at the National Zakat Agency (BAZNAS) of Wajo Regency - Faisal; Aldi Setiawan; Andi Yuniarti (Jurnal Ilmu Manajemen Profitability, 2026)
This study examined the effect of service quality on muzakki decision-making at Badan Amil Zakat Nasional (BAZNAS) of Wajo Regency, Indonesia. Despite the substantial potential of zakat as an instrument for social welfare and poverty reduction, the actual participation of muzakki in institutional zakat payment remains relatively low, indicating the need to identify factors influencing their decisions. This research aimed to analyze whether service quality significantly influences muzakki decisions to pay zakat through BAZNAS. A quantitative causal-associative design was employed, using primary data collected through questionnaires distributed to 99 muzakki selected through simple random sampling from a population of 228 individuals. The data were analyzed using simple linear regression with SPSS, following validity and reliability testing of the SERVQUAL-based instrument covering tangibles, reliability, responsiveness, assurance, and empathy. The results showed that service quality had a positive and significant effect on muzakki decision-making (t = 2.048; p = 0.043 < 0.05), with the regression equation ? = 42.177 + 0.116 ? Y=42.177+0.116X. The correlation coefficient (r = 0.204) indicated a weak but significant relationship, and the coefficient of determination (R² = 0.041) suggested that service quality explained 4.1% of decision variance. These findings imply that improving professional, responsive, and transparent services strengthens trust and encourages institutional zakat participation, contributing practically to service strategy development and theoretically to behavioral studies in Islamic social finance.